Experiences of Grade 12 EFAL teachers' Assessment of Literature Set-works in Limpopo Secondary Schools - Emsley, Maletsema Ruth (University of Limpopo, 2017)
South Africa has embarked on the official inclusion of school-based assessment in all subjects for transforming once-off pen and paper testing to redress the past rigid, norm-referenced, unreliable and non-transparent discriminative educational assessment in schools. The introduction does not only aim at offering constant constructive feedback to learners to improve performance, but it also assists teachers to diagnose, facilitate and improve on their assessment methods, to report learner performance to relevant stakeholders like parents, schools, districts and lastly national departments of education and to inform teaching and more assessments. Over and above it forms 25% of the total mark for all subjects in further education and training including Grade 12. There is compelling empirical evidence that school-based assessment positively influences the performance of learners in large scale assessments. In spite of its significance, the school-based assessment of literature set-works has received scant attention in secondary schools. Despite the local and international interest and implementation of school-based assessment nowadays, its administration in South Africa schools still remains a challenge. This study therefore followed an interpretive qualitative approach to respond to the question: What are the experiences of English first additional language teachers in assessment of literature set-works in secondary schools in Limpopo province? The teacher self-efficacy theory guided this study. It was not only used to substantially explain the stature of a literature teacher, but also to generate strategies to promote teacher flexibility and application of assessment practices in English first additional language. The theoretical and practical implications of self-efficacy theory are discussed in terms of their relevance to both the literature teacher and school-based assessment expectations. Multiple qualitative data collection methods of focus group interviews, openended questionnaires, documents and field notes were employed to strengthen findings in a natural setting. Respondents were selected through the purposive sampling. Five districts of Limpopo province were sampled for this study: four focus group interviews were conducted, 139 open-ended questionnaires were returned and documents relevant to answering the research question were analysed. Data were transcribed and then analysed by the Tesch (1990) method (as in Creswell 1994) of qualitative data analysis and constant comparison method. Teachers operating in the assessment of English first additional language have acknowledged the importance of school-based assessment, moderation and literature set-works, however they still feel literature assessment in schools does not receive the attention it deserves. The qualitative data revealed that teachers face various challenges in the implementation of school-based assessment of literature set-works. Most teachers through their responses still face challenges of time, resources and curriculum advisory support, inability to design their own literature set-works tasks, learner illiteracy and lack of teacher efficacy. Moreover, teachers are keenly dependent on previously written question papers. Findings have further shown that teachers suffer the pressures of authorities who impose extra assessment work on them and the selected literature prescribed works that stay for too long in the curriculum – these comprise the programme of assessment. These findings, although they may not be generalised, might contribute to prospect future research and educational change in assessment of literature set-works in schools. Various recommendations have been made for educational stakeholders in further research prospects and future improvement on assessment of literature set-works in schools emphasizing the independence of English literature setworks
Thesis (PhD. (Education)) --University of Limpopo, 2017.
Keywords: Assessment; School-based assessment; Literature; Moderation; Teacher efficacy; English Language--Study and Teaching.; Teachers--Language.; Curriculum-based assessment.; Education evaluation.; Academic performance.